2017
DOI: 10.20886/jphh.2017.35.2.115-122
|View full text |Cite
|
Sign up to set email alerts
|

Honeycombing and Deformation of Six Wood Species and Their Relationship With Several Physical

Abstract: It is presumed that the wood susceptibility to drying defects is related to several physical properties. This paper examines the drying defects: honeycombing and deformation of six wood species (trema, fast growing teak, bayur, jabon, angsana and lamtoro) during high temperature drying and analyses their relationship with initial moisture content, T/R shrinkage ratio and density. Terazawa method was used to examine the defect during high temperature drying. Result shows that after high temperature drying, lamt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Unfortunately, its dimension is not yet stable. Yuniarti, Basri, and Abdurachman (2017) reported that the ratio of shrinkage in the tangential direction against radial direction (T/R ratio) of the 5year-aged un-densified JUN wood was very high (about 3). Dimensional stability, presented by the T/R ratio, presents one of the wood properties that should be considered in determining the wood uses.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, its dimension is not yet stable. Yuniarti, Basri, and Abdurachman (2017) reported that the ratio of shrinkage in the tangential direction against radial direction (T/R ratio) of the 5year-aged un-densified JUN wood was very high (about 3). Dimensional stability, presented by the T/R ratio, presents one of the wood properties that should be considered in determining the wood uses.…”
Section: Resultsmentioning
confidence: 99%